Model for Strengthening Homestays based on Traditional Houses in the Development of Community-Based Tourism in the Gebong Memarong Tourism Village - Hardyanti; Muhammad Afif Tarjih; Devylia (Jurnal Sains Terapan Pariwisata, 2026)
This study aims to develop a model for strengthening traditional house-based homestays within the framework of community-based tourism (CBT) in the Gebong Memarong tourist village. The traditional houses of the oldest tribe in Bangka are positioned as assets with the potential to become community-based accommodations. This study uses a descriptive qualitative approach through in-depth interviews, participatory observation, and documentation with thematic analysis. The results of this study indicate that homestay strengthening is carried out through three main pillars: increasing human resource capacity, optimizing cultural and environmental values, and strengthening community-based governance through multi-stakeholder collaboration. Traditional houses also function as cultural interpretations that enrich the tourist experience. The main challenges include limited infrastructure, human resource capacity, and access to digital promotion. Therefore, sustainable cross-sector collaboration is needed. This study offers a conceptual model for integrating traditional houses in the development of community-based homestays that can be replicated in other tourist villages.